Experiential Learning through Field Trips: Effects on Educational, Social and Personal Development among Linguistics Majors - Yvonne Michelle, Campbell; Remmy, Gedat (UNIMAS Publisher, 2021)
The study explores a group of university students' perceptions towards field trips and the effect on their educational, social, and personal development. Data was collected using questionnaires and it has revealed that participants' overall perception of field trips was positive. Findings showed that participants preferred certain aspects of the field trips, particularly those on gaining new experiences and the opportunity to apply what they have learned. It helped improve their knowledge, interest, confidence, communication skills, social training, and awareness of the world around them. However, the least liked aspects were the pre-and post- activities, group size and time allocation. Future studies may want to examine and compare a more varied sampling of students from various fields and perceptions of different genders.